Strength and deformation characteristics of recycled polyethylene fibre reinforced concrete - Ghadafi, Abdullai Mohammed (2017)
A thesis submitted to the Department of Civil Engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy in Structural Engineering.